Establishing the diagnosis of fournier gangrene using the modified laboratory risk indicator for necrotizing fasciitis (LRINEC) score in children: A case report - Qomariah, Laily Noor; Asri Yuniarti; Triyoga; He-Yeon Asva Nafaisa; Agnes Sri Siswati (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
Fournier’s gangrene (FG) is a form of necrotizing fasciitis that affects the genital and perineal areas. It is rare case in children and is often difficult to diagnose early, contributing to high morbidity and mortality. Prompt diagnosis and aggressive management are essential to reduce life-threatening complications. We report 2 mo. male infant presented with fever and an abrupt onset of rapidly spreading erythematous rash. Laboratory examinations showed leukocytosis, anemia, neutrophilia, hyponatremia, and elevated C-reactive protein (CRP) levels. An evaluation was performed using the pediatric laboratory risk indicator for necrotizing fasciitis (P-LRINEC), a modified version of the LRINEC score. The patient had a total score of 10, indicating a high risk of necrotizing fasciitis. The patient underwent immediate debridement and empirical antibiotic therapy. A 2 wk post-therapy evaluation showed significant clinical improvement. Fournier’s gangrene in children often resembles other skin infections, making early diagnosis difficult. The 3 main characteristics of FG are sudden onset, rapid progression, and lack of a clear specific cause. The P-LRINEC score is a diagnostic tool that can aid in the early detection of FG in children. This case highlights the importance of early recognition and management of Fournier’s gangrene in children using the P-LRINEC score, which is more appropriate for pediatric patients, to enable timely intervention. Increased clinical awareness and further validation through larger-scale studies are needed.